2020
DOI: 10.15376/biores.15.1.1547-1562
|View full text |Cite
|
Sign up to set email alerts
|

Durability of wood treated with propolis

Abstract: Propolis is an important antifungal agent found naturally in beehives and used as a food supplement for many purposes. This study aimed to use methanolic propolis extract (MPE) as a treatment material as an antifungal agent for wood preservation. Scots pine and paulownia woods were exposed to Trametes versicolor and Neolentinus lepideus fungi for 12 weeks, and untreated woods were used as the controls. Compared with the control, paulownia wood exposed to N. lepideus had a 47.2% mean mass loss, while the treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In order to increase the resistance of wood to biotic conditions, various types of preservatives are used, and currently, preparations based on natural substances are becoming more and more popular, e.g., propolis extract [ 27 , 28 ]. The literature data confirmed that wood treated with propolis extract and a mixture of propolis extract and silicon compounds showed resistance to wood-decay fungi, including C. puteana [ 28 , 30 , 48 ]. In addition, wood used as a filler in wood composites are often modified or treated with preservatives to obtain resistance of WPCs against wood destructive microorganisms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to increase the resistance of wood to biotic conditions, various types of preservatives are used, and currently, preparations based on natural substances are becoming more and more popular, e.g., propolis extract [ 27 , 28 ]. The literature data confirmed that wood treated with propolis extract and a mixture of propolis extract and silicon compounds showed resistance to wood-decay fungi, including C. puteana [ 28 , 30 , 48 ]. In addition, wood used as a filler in wood composites are often modified or treated with preservatives to obtain resistance of WPCs against wood destructive microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…The stabilization of Xc results for systems containing modified wood can be explained by the protective effect of propolis. The activity of propolis against decay fungi has been studied and published many times [ 28 , 30 , 33 ]. There have also been many studies showing that propolis is a material capable of absorbing UV radiation [ 76 , 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Propolis is a natural paste as a result of the accumulation of resinous substances collected from the bark, leaves and stems of the honey bees in the hives. This complex mixture, which is used to protect the hive for multiple purposes, is an indispensable natural bee product of apitherapy (Akçay, Birinci, Birinci, & Kolaylı, 2020;Bankova et al, 2019). It is known that the best solvent for raw propolis is 70% ethanol, but some glycol derivatives and vegetable oils are also usedin the preparation of extracts (González-Búrquez et al, 2018;Oroian, Ursachi, & Dranca, 2020).…”
Section: Introductionmentioning
confidence: 99%